Symbolic Interaction Between Personal Trainers and Members At Celebrity Fitness Express Teras Kota BSD - Utomo, Ardian Setio; Asgawanti, Eka Desy; Kuswarno, Engkus; Suryana, Asep (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
Celebrity Fitness is a company operating in the largest fitness world in Asia. This research aims (1) To understand further how personal trainers communicate when welcoming members, (2) To understand further how personal trainers use communication when training with members, (3) To understand further how personal trainers use communication in attracting members interest in training, (4) To be able to understand how members perceive the communication used by personal trainers. The research was carried out using a qualitative approach with participant observation to observe the communication between personal trainers and members. In answering this problem, researchers used a symbolic interaction theory approach and conversation analysis through an interpersonal communication process using verbal and nonverbal communication. As a result of this research, researchers constructed personal trainer communication into three categories, namely, personal trainers always pay attention to members both in terms of feelings and health, personal trainers also educate members by providing explanations about everything regarding the field of fitness and professional advice to members, and personal trainers always remind members of their mutually agreed training schedule and fitness goals. Meanwhile, members perceptions of the communication carried out by personal trainers are good. for members, the appearance of a personal trainer is the most important thing, as is an athletic body shape and always appearing fashionable in clothing. She was followed by good skills in the world of fitness, a polite, friendly attitude, and always looking energetic.